The developmental origins of a default moral response: A shift from honesty to dishonesty. Issue 4 (21st March 2022) - Sai, Liyang; Shang, Siyuan; Zhao, Changzhi; Liu, Xinchen; Jiang, Yuanyuan; Compton, Brian J.; Fu, Genyue; Heyman, Gail D.
Abstract: People are sometimes tempted to lie for their own benefit if it would not harm others. For adults, dishonesty is the default response in these circumstances. The developmental origins of this phenomenon were investigated between 2019 and 2021 among 6‐ to 11‐year‐old Han Chinese children from China ( N = 548, 49% female). Children had an opportunity to win prizes in a behavioral economics game (Experiment 1) or a temptation resistance game adapted from developmental psychology (Experiment 2). In each experiment, the youngest children showed a default tendency of honesty and there was an overall age‐related shift toward a default tendency of dishonesty. These findings provide direct evidence of developmental change in the automatic and controlled processes that underlie moral behavior.